Teknik Pemeriksaan Hip Joint Proyeksi Anterior Posterior dengan Kasus Post Orif Total Hip Replacement di Instalasi Radiologi RSUDMeuraxa Kota Banda Aceh - Pocut Zairiana Finzia; Firrizqi (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
This study aims to determine the hip joint examination technique in Post ORIF Total Hip Replacement cases at the Radiology Installation of Meuraxa Hospital, Banda Aceh. Hip joint examination is performed with anterior, posterior, and axial projections in Post ORIF Total Hip Replacement cases using AP pelvic projection. This study is qualitative with a case study approach. Data collection methods include observation, interviews, and documentation. The research subjects were one radiologist, three radiographers, and one patient with Post ORIF Total Hip Replacement cases. AP pelvic radiography examination at the Radiology Installation of Meuraxa Hospital, Banda Aceh aims to compare the right or left hip.